2016
DOI: 10.3762/bjoc.12.118
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of tricyclic compounds by intramolecular palladium-catalyzed addition of aryl iodides to carbonyl groups

Abstract: SummaryStarting from γ-ketoesters with an o-iodobenzyl group we studied a palladium-catalyzed cyclization process that stereoselectively led to bi- and tricyclic compounds in moderate to excellent yields. Four X-ray crystal structure analyses unequivocally defined the structure of crucial cyclization products. The relative configuration of the precursor compounds is essentially transferred to that of the products and the formed hydroxy group in the newly generated cyclohexane ring is consistently in trans-arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…19 This is presumably followed by proton transfer from adventitious water to release hemiketal 4. Notably, similar reactions of Pd, 20 Ru, 21 and Co 22 σ-aryl species have been reported. The resulting TpNi II fragment then likely undergoes disproportionative ligand exchange to yield the observed Tp 2 Ni byproduct along with Ni II (solvent) 4 2+ .…”
supporting
confidence: 72%
“…19 This is presumably followed by proton transfer from adventitious water to release hemiketal 4. Notably, similar reactions of Pd, 20 Ru, 21 and Co 22 σ-aryl species have been reported. The resulting TpNi II fragment then likely undergoes disproportionative ligand exchange to yield the observed Tp 2 Ni byproduct along with Ni II (solvent) 4 2+ .…”
supporting
confidence: 72%
“…As is the case for donor–acceptor cyclopropanes, ring opening and expansion protocols exploiting the inherent ring strain of bicyclo[3.1.0]hexane and bicyclo[4.1.0]heptane derivatives have been reported. 27 To this end, we also demonstrated that both aza- and oxa-bicyclo[4.1.0]heptanes prepared using the photochemical cyclopropanation process described herein readily underwent ring expansion reaction with hydrazine to afford valuable heterocyclic frameworks ( Scheme 3b ). 28 Due to the facile and catalyst-free nature of the [2 + 1]-photocycloaddition process, the development of additional telescoping strategies to rapidly generate molecular complexity are currently under investigation.…”
Section: Resultsmentioning
confidence: 72%
“…The formation of Mukaiyama aldol products 9a , b in 78–90% yields supports the tendency of the palladium enolate to undergo nucleophilic addition in an intermolecular fashion on the carbonyl functionality, even if the substrate is electronically different from 1a . Recently, nucleophilic addition of an arylpalladium complex, which is a weaker nucleophile than palladium enolate species, to carbonyl groups in an intramolecular fashion has been reported, although the corresponding intermolecular version is not known …”
Section: Resultsmentioning
confidence: 99%
“…Recently, nucleophilic addition of an arylpalladium complex, which is a weaker nucleophile than palladium enolate species, to carbonyl groups in an intramolecular fashion has been reported, although the corresponding intermolecular version is not known. 45 A limited set of experiments was performed to understand the possible mechanism behind the Mukaiyama-type aldol addition (Scheme 5 and Table 2). The addition product 3a did not form upon excluding Pd(OAc) 2 from the reaction mixture, which indicated the necessity of the transition metal catalyst to forge the C−C bond between quinone and enoxysilane substrates (Scheme 5; eq 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%